SWOT ANALYSIS IN PREPARING STRATEGIC PLANS FOR IMPROVING THE QUALITY OF EDUCATION - Sari, Yunita; Muh. Saidil Ikhwan (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2024)
This article discusses SWOT analysis as an effective tool in developing strategic plans to improve the quality of education. This research conducted at SMA Negeri 1 Sijuk. Through a SWOT (strengths, weaknesses, opportunities and threats) approach, this research identifies school strengths, such as the presence of quality teachers and adequate infrastructure, which can be the basis for strategic improvement. In the other hand, weaknesses in terms of limited operational funds and limited access to technology are also analyzed to find the right solution. Opportunities to improve the quality of education are seen through the development of professional teacher programs and the potential for strong support from parents and the community. However, this article also discusses threats it may face, including changes in educational policy and competition with other schools. By outlining this SWOT analysis, this article provides a comprehensive strategic basis for SMA Negeri 1 Sijuk to formulate an effective strategic plan in achieving a holistic improvement in the quality of education.